Efektivitas Peningkatan Penerimaan Pajak Daerah di Wilayah Lahan Basah Berbasis Pola Pikir Religius - Juniar, Asrid; Rahmawati, Rini; Wardhana, Ali; Hamdani, Hamdani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Taxes are the largest source of revenue for the Indonesian state. Taxes also have a large contribution to the development of all regions in Indonesia. Taxes in Indonesia consist of central taxes and regional taxes. South Kalimantan Province which consists of 13 districts/cities. South Kalimantan Province is one of the areas with wetland topography in Indonesia. One of the areas with the largest peatlands according to data from the Central Statistics Agency is Tapin Regency and the majority of the population is Muslim, so religious nuances are always visible. The potential for regional tax revenue in Tapin Regency, which is one of the areas with wetland topography and a religious population, makes this research interesting because based on the results of existing research, it still shows research gaps so that research related to the effectiveness of regional tax revenue in wetland areas is pattern-based. religious thought becomes important. This research includes quantitative research. The data used is primary data from respondents as informants with a sample size of 200 respondents. The data analysis technique uses partial least squares to analyze the influence of religiosity on taxpayer compliance and the effectiveness of local tax revenues. The research results show that religiosity has a significant effect on taxpayer compliance and the effectiveness of tax revenue. Taxpayer compliance also has a significant effect on the effectiveness of tax revenue in the Tapin district area.